2011
DOI: 10.1002/jpln.201000341
|View full text |Cite
|
Sign up to set email alerts
|

Response of five citrus rootstocks to iron deficiency

Abstract: Citrus established in calcareous soils can be affected by iron (Fe)‐deficiency chlorosis which limits yield and the farmers' income. The degree of deficiency depends on the rootstock, but the resistance to Fe chlorosis still requires further investigation. To study physiological parameters of citrus rootstocks that could be used to evaluate resistance to Fe deficiency, plants of Troyer citrange (Citrus sinensis L. Osb. × Poncitrus trifoliata L. Raf.), Carrizo citrange, Volkamer lemon (Citrus volkameriana Ten. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 23 publications
3
22
0
6
Order By: Relevance
“…It is known that a low Fe supply negatively affects the chlorophyll content and other components of chloroplasts, which reduces growth capacity (De La Guardia and Alcantara, 2002). In the present study, it was observed that as iron doses rise, SPAD values increase, which is supported by other research findings (Pestana et al, 2001;De La Guardia and Alcantara, 2002;Pestana et al, 2011). This is because iron functions as a component of proteins in significant cellular events such as respiration and cell division; moreover, it has a role in the reduction steps of important biological events, such as transpiration and photosynthesis, and also in chlorophyll biosynthesis (Einsenstein and Blemings, 1998;Zocchi et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…It is known that a low Fe supply negatively affects the chlorophyll content and other components of chloroplasts, which reduces growth capacity (De La Guardia and Alcantara, 2002). In the present study, it was observed that as iron doses rise, SPAD values increase, which is supported by other research findings (Pestana et al, 2001;De La Guardia and Alcantara, 2002;Pestana et al, 2011). This is because iron functions as a component of proteins in significant cellular events such as respiration and cell division; moreover, it has a role in the reduction steps of important biological events, such as transpiration and photosynthesis, and also in chlorophyll biosynthesis (Einsenstein and Blemings, 1998;Zocchi et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Esto da a entender que la aplicación del Se en plantas, como práctica cultural, se relaciona en parte con el tamaño de los frutos. Estudios anteriores realizados también en el cultivo de la fresa, como el de Correia et al (2011), han llegado a conclusiones similares, señalando además que ciertas prácticas culturales pueden influir en la composición nutricional de los frutos. De forma similar, el Se también se relaciona con la firmeza de la fruta.…”
Section: Resultados Y Discusiónunclassified
“…En la Figura 2-A puede observarse una disminución de los valores de SPAD en hoja vieja desde la semana 18 a la semana 25, que se corresponde con el final del ciclo de cultivo. Tendencias similares han sido descritas por Pestana et al (2011), que sugirieron cambios en la concentración total de clorofila (mol m -2 ) de las hojas de plantas de fresa a lo largo del ciclo del cultivo. Según los resultados obtenidos se observó un efecto significativo de los tratamientos de Se y de las semanas sobre los valores de SPAD en hoja vieja.…”
Section: -Eunclassified
“…In our conditions, salt treatment under both Fe supply regimes apparently restricts iron uptake, as evidenced by the lower iron concentrations (mg g À1 DW) in leaves and to lesser extent in roots of salt-treated plants. These results could be explained by the dilution effect related to the biomass increase of salt-treated plants [44,45] rather by a salt-induced limitation of Fe uptake. This assumption is strengthened when analyzing data in terms of Fe content (mg plant À1 ) which show either significantly higher or constant values following salt treatment depending on the organ.…”
Section: Discussionmentioning
confidence: 99%